The Role of Pharmacological Treatment in the Chemoreflex Modulation - Langner-Hetmańczuk, Anna; Tubek, Stanisław; Niewiński, Piotr; Ponikowski, Piotr (Frontiers in Physiology, 2022)
From a physiological point of view, peripheral chemoreceptors (PCh) are the main sensors of hypoxia in mammals and are responsible for adaptation to hypoxic conditions. Their stimulation causes hyperventilation – to increase oxygen uptake and increases sympathetic output in order to counteract hypoxia-induced vasodilatation and redistribute the oxygenated blood to critical organs. While this reaction promotes survival in acute settings it may be devastating when long-lasting. The permanent overfunctionality of PCh is one of the etiologic factors and is responsible for the progression of sympathetically-mediated diseases. Thus, the deactivation of PCh has been proposed as a treatment method for these disorders. We review here physiological background and current knowledge regarding the influence of widely prescribed cardiovascular medications on PCh acute and tonic activities.